Ubiq-exp: A toolkit to build and run remote and distributed mixed reality experiments - Steed, Anthony; Izzouzi , Lisa; Brandstätter , Klara; Friston, Sebastian; Congdon , Ben; Olkkonen, Otto; Giunchi , Daniele; Numan , Nels; Swapp , David (Frontiers in Virtual Reality, 2022)
Developing mixed-reality (MR) experiments is a challenge as there is a wide variety of functionality to support. This challenge is exacerbated if the MR experiment is multi-user or if the experiment needs to be run out of the lab. We present Ubiq-Exp - a set of tools that provide a variety of functionality to facilitate distributed and remote MR experiments. We motivate our design and tools from recent practice in the field and a desire to build experiments that are easier to reproduce. Key features are the ability to support supervised and unsupervised experiments, and a variety of tools for the experimenter to facilitate operation and documentation of the experimental sessions. We illustrate the potential of the tools through three small-scale pilot experiments. Our tools and pilot experiments are released under a permissive open-source license to enable developers to appropriate and develop them further for their own needs.